2016
DOI: 10.1332/174426415x14358305421172
|View full text |Cite
|
Sign up to set email alerts
|

Evidence, fidelity, and organisational rationales: multiple uses of Motivational Interviewing in a social services agency

Abstract: In discussions and empirical investigations of the implementation of evidence-based interventions there is often a narrow focus on treatment fidelity. Studying a social services agency trying to incorporate Motivational Interviewing (MI), commonly regarded as evidence-based, this paper problematises a one-sided attention to treatment fidelity by showing how non-fidelity can be constructive from an organisational perspective. While treatment fidelity is one important aspect, it is argued that there might be oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Timmermans & Mauck, 2005), and the logic of fluidity with demands on individualisation and responsibilisation (Andersen & Järvinen, 2007;Järvinen & Mik-Meyer, 2012), and with practical feasibility and patient-centred care (Epstein et al, 2010). There is thus one 'desktop product RP' providing political legitimacy, and one 'real life RP' that provides professional legitimacy (for a similar reasoning on Motivational Interviewing, see Björk, 2016). According to Mol and Berg (1994), the coexistence of different logics, often referred to as the difference between principles and practice, is common in medicine and similar disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Timmermans & Mauck, 2005), and the logic of fluidity with demands on individualisation and responsibilisation (Andersen & Järvinen, 2007;Järvinen & Mik-Meyer, 2012), and with practical feasibility and patient-centred care (Epstein et al, 2010). There is thus one 'desktop product RP' providing political legitimacy, and one 'real life RP' that provides professional legitimacy (for a similar reasoning on Motivational Interviewing, see Björk, 2016). According to Mol and Berg (1994), the coexistence of different logics, often referred to as the difference between principles and practice, is common in medicine and similar disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have highlighted the importance of organizational support as an explicit facilitator for an intervention's implementation (Mosson et al, 2017;Rojas & Stenström, 2020). Other factors facilitating an intervention's success in an organization would be how well it fits with the routines and practices of the organization (Björk, 2016b) and staff possessing sufficient knowledge to search for evidence or to systematically follow up interventions (Rojas & Stenström, 2020).…”
Section: The Organization Of Social Work and Evidence-based Practicementioning
confidence: 99%
“…However, systematic reviews have shown that many studies lack fidelity measures or are otherwise of low quality, making it difficult to assess MI efficacy in relation to specific mediators of change (Apodaca & Longabaugh, 2009;Copeland, McNamara, Kelson, & Simpson, 2015). Nevertheless, there is a tendency to linkages between specific MI practice behavior (including MI spirit), client change talk, and outcomes-which in turn is dependent on MI training as well as systemic changes in the treatment context (Miller & Moyers, 2015, 2016. Still, there is not enough evidence on the association between MITI assessment and MI outcomes (Moyers, Rowell, Manuel, Ernst, & Houck, 2016).…”
Section: Motivational Interviewing: the Development Of A Bfluid^intermentioning
confidence: 99%
“…But even in instances where nurses reported using an MI style approach, not everyone had MI training or scored high enough in MITI evaluation (Östlund, Kristofferzon, Häggström, & Wadensten, 2015). Professionals may also use MI differently depending on their organizational position or use only certain MI techniques and not necessarily in the spirit of MI, due to their perception that it does not fit with the organization's routines and practices (Björk, 2016). Miller and Rollnick (2014) suggest that interventions should comprise proficiency thresholds prior to treating patients, ongoing feedback, and coaching, as well as fidelity levels which need to be obtained throughout delivery.…”
Section: Context Mattersmentioning
confidence: 99%